Institutional Image of a Community University - Behling, Hans Peder; Hostins, Regina Celia Linhares; Ramos, Mayara Bonin; Bazzanello, Vagner Luis (Comunicação & Educação, 2022)
This study was motivated by the inquiry about the possible (in)coherence between the way Community Universities communicate their community attributes and the image perceived by their respective audiences. The general objective is to analyze the institutional image of a Community University in the view of the internal and external community. The method adopted is qualitative in nature, based on Jung's Archetypes Theory on the construction of the collective unconscious and its expression in the perception of the institutional image. Empirical data were collected through interviews of focal groups, organized by different audiences with direct and/or indirect linkage to the institution. Among the results of the research stands out the expressive and convergent perception of the interviewees about the archetypes of the Common Man and the Caregiver, which summarize as main perceived attributes of the institution: responsible, simple, adaptable, collective, friend, worker, modest, protective, reliable, solidary and helpful, with important link to the concept of community university.